2020
DOI: 10.3389/fcell.2020.00818
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Autoimmune-Mediated Eye Diseases

Abstract: MicroRNAs (miRNAs) are evolutionarily conserved short non-coding RNAs that act at post-transcriptional regulation of gene expression by destroying target messenger RNA or inhibiting its translation. Recently, miRNAs have been identified as important regulators in autoimmunity. Aberrant expression and function of miRNAs can lead to dysfunction of immune system and mediate autoimmune disorders. Here, we summarize the roles of miRNAs that have been implicated in three representative ocular autoimmune disorders, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 96 publications
(102 reference statements)
0
21
0
Order By: Relevance
“…In addition, miRNAs could also bind the 5'UTR region and the promoter region, inducing translational activation [9]. A key role of microRNAs in the regulation of the immune response has been highlighted, so it is not surprising that aberrant expression of miRNAs has been demonstrated in numerous autoimmune diseases [10,11], included SS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miRNAs could also bind the 5'UTR region and the promoter region, inducing translational activation [9]. A key role of microRNAs in the regulation of the immune response has been highlighted, so it is not surprising that aberrant expression of miRNAs has been demonstrated in numerous autoimmune diseases [10,11], included SS.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 36 The exact mechanism in the progression of TAO is unclear although several studies implicate TSHR and IGF-1R, which are both upregulated in the OFs of patients with TAO. 5 , 37 The miRNA regulation of genes involved in TAO is gaining interest, 38 therefore, in our study, we focused on miRNA that may be involved in the regulation of the inflammasome in TAO using relevant markers such as NLRP3. We found a number of miRNAs that were differentially regulated in the orbital connective tissue of TAO patients and confirmed that three of these were significantly upregulated (miR-22, miR-27b, and miR-378) and one was significantly downregulated (miR-143).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can regulate more than 60% of protein- coding genes in the humans and have been implicated in the various biological processes such as the lineage commitment in the immune system, cell proliferation, differentiation, apoptosis, and maintenance of immune homeostasis ( 56 , 57 ). An abnormal expression of miRNAs has been closely related to the pathogenesis of various autoimmune-mediated eye diseases such as GO ( 58 ). Circulating miRNAs can be detected in the peripheral blood and orbital tissues of GO patients, with different expression levels in the active disease stage of GO.…”
Section: Non-coding Rnas and Gomentioning
confidence: 99%